2020
DOI: 10.1177/1359105320963211
|View full text |Cite
|
Sign up to set email alerts
|

Self-image and social-image of the donors: Two different views from oocyte donors’ eyes

Abstract: To identify the perceptions of women oocyte donors this qualitative study was conducted on 30 oocyte donors using in-depth interview. The three main categories of decision-making challenge, the consequences of participation in assisted reproductive treatment, and the contrast between the self-image and social-image of the donor were inferred. Financial and altruistic motivation, social taboo, and the approval of trusted people were the sub-categories of the decision-making challenge. The results of the study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…In ART through using donated oocytes, oocyte donors are selected from among young women in order to obtain an appropriate number of oocytes with high fertility potential and increase the treatment success. Moreover, as studies have shown that the oocyte donor’s participation in ART is mainly because of financial motivations [ 1 , 3 , 11 ], the lower economic condition of this group can be justified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In ART through using donated oocytes, oocyte donors are selected from among young women in order to obtain an appropriate number of oocytes with high fertility potential and increase the treatment success. Moreover, as studies have shown that the oocyte donor’s participation in ART is mainly because of financial motivations [ 1 , 3 , 11 ], the lower economic condition of this group can be justified.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread use of the third party in assisted reproductive techniques (ART) and the success of infertility treatment following its use has led to an increased number of women volunteers who enter the oocyte donation process [ 1 ], mainly for financial reasons and altruism [ 2 , 3 ]. This process leads to the creation of a creature that is the genetic offspring of the donor and may inherit the thoughts and feelings of the genetic mother.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reluctance of the recipient couples, especially women, to disclose the resulting offspring's genetic origin [13], concerns about the physical and mental health of the donor [14], decreased self-concept [15], concerns about the outcome of the treatment [16], ethical and religious issues [17], and economic and social challenges [18] are among the most known problems of using this technique. Furthermore, the significance of fertility as the most prominent gender-related role of women in traditional societies leads to new dimensions of social challenges for women in these societies [19].…”
Section: Introductionmentioning
confidence: 99%